STUDI RELASI HIDRODINAMIKA SUNGAI CIWALEN DAN AIR TANAH MELALUI PENDEKATAN MODEL (Studi Kasus pada Aliran Sungai Ciwalen Kecamatan Garut Kota) - Asep Mulyono (Widyariset, 2010)
Ciwalen River flows pass of leather industry in Sukaregang area that is the one of the prominent industry in Garut region. The usage of chemicals in the leather tanning process resulted in toxic liquid waste released to Ciwalen River. Ciwalen River containing contaminants would further contaminate the groundwater system along the Ciwalen River. The study of groundwater flow particularly hydrodynamic relation river and groundwater surrounding is required. Field and secondary data were utilized in this study. Groundwater flow and hydrodynamic relation river and groundwater analyses were carried out using Visual Modflow v3.1. software. The study results that hydrodynamic relationship between Ciwalen River and the groundwater system can be divided into 6 segments. Segment 1, 4, and 6 belong to effluent type, while segment 2 is of influent type. Segment 3 and 5 located right of the river are effluent and those located in the left of the river are of influent type. River channel length of segment 1 are 0.95 km, length of segment 2 are 0.62 km, length of segment 3 are 0.88 km, length of segment 4 are 0.21 km, length of segment 5 are 0.63 km and length of segment 6 are 1.18 km. Influent type indicate causes a groundwater pollution because river that’s containing contaminants would further contaminate the roundwater system particularly at urban wells in surrounding segment.